Comparative Analysis of Primary Closure Versus Ileostomy in the Surgical Management of Typhoid Intestinal Perforation - Hussan, Shahid; Shabbir, Asiya; Aftab, Muhammad Farrukh; Rauf, Abdul; Akhtar, Naveed; Rasheed, Uzma (Biological and Clinical Sciences Research Journal, 2025)
Typhoid fever remains a significant public health concern in low and middle-income countries, particularly in overcrowded and resource-limited settings. In Pakistan, the emergence of multidrug-resistant Salmonella Typhi strains has increased the severity and complications associated with the disease. Intestinal perforation is a common and life-threatening complication requiring urgent surgical intervention. Literature presents conflicting evidence regarding the superiority of primary repair versus ileostomy in the management of typhoid perforation. This study was designed to compare early outcomes of these two surgical approaches. Objective: To evaluate and compare the short-term outcomes of primary repair versus ileostomy formation in patients undergoing surgery for typhoid-related intestinal perforation. Methods: This randomized controlled trial was conducted in the Department of Surgery at Nishtar Medical University/Hospital, Multan, over six months, following ethical approval. A total of 40 patients who met the inclusion and exclusion criteria were enrolled and randomized into two groups. Group A underwent primary repair of the perforation, while Group B received ileostomy formation. Patients were followed postoperatively for 7–10 days, and outcomes, including wound infection, mortality, and duration of hospital stay, were recorded. Results: Wound infection occurred in 11 (55%) patients in the primary repair group and in 4 (20%) patients in the ileostomy group (p = 0.022). Mortality was noted in 3 (15%) patients in the primary repair group compared to 1 (5%) patient in the ileostomy group (p = 0.292). The mean hospital stay was significantly longer in the primary repair group (7.15 ± 2.18 days) compared to the ileostomy group (5.70 ± 1.34 days) (p = 0.017). Conclusion: In the short-term postoperative period, ileostomy formation was associated with significantly lower wound infection rates and shorter hospital stay compared to primary repair in patients with typhoid intestinal perforation. These findings support the use of ileostomy as a preferred initial surgical approach in such cases.